2010
DOI: 10.1530/eje-10-0528
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preterm birth and small birth size on serum anti-Müllerian hormone levels in young adult women

Abstract: Background/objectives: Preterm birth has been associated with reduced reproduction rates, and controversies remain regarding the effect of being born small for gestational age (SGA) on ovarian function. Recent findings in young men showed no effect of preterm and SGA birth on testis function. We hypothesised that follicle pool size in young adult women is also not affected by preterm and SGA birth. Design/methods: In 279 young women of the PROGRAM/PREMS study, aged 18-24 years, the influence of gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 37 publications
6
24
1
Order By: Relevance
“…Our finding that AMH levels are higher among women who matured earlier is consistent with a study by Kerkhof et al (2010), who similarly reported an inverse association between AMH levels in young adulthood and menarcheal age. The authors proposed that this might be owing to girls who have larger follicle pools having higher estrogen levels, which could lower the age of first menses, a possibility supported by findings suggesting that AMH might be involved in the regulation of estrogen synthesis (Kevenaar et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that AMH levels are higher among women who matured earlier is consistent with a study by Kerkhof et al (2010), who similarly reported an inverse association between AMH levels in young adulthood and menarcheal age. The authors proposed that this might be owing to girls who have larger follicle pools having higher estrogen levels, which could lower the age of first menses, a possibility supported by findings suggesting that AMH might be involved in the regulation of estrogen synthesis (Kevenaar et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that AMH, a proxy for ovarian reserve, is related to indices of life history scheduling (menarcheal age) and reproductive effort (parity) (Ellison, 2003) in young adult women. AMH levels in this population were similar to those from 24-year-old women in the United States (mean 5 4.1 ng/mL, Seifer et al, 2011), but they were considerably lower than the levels reported among 18-to 22-year-old women in the Netherlands (median 5 7.6 ng/mL, Kerkhof et al, 2010). The limited comparative data from women matched by age, and differences in laboratory protocol across studies, preclude drawing strong conclusions from these crosspopulation differences.…”
Section: Discussionsupporting
confidence: 55%
“…The Avon Longitudinal Study of Parents and Children (ALSPAC) found paternal, but not maternal, smoking prior to and during pregnancy to be associated with lower AMH levels in adolescent females (ages 14–16) (33). A smaller study of young women (n=279), ages 18–24, conducted in the Netherlands, found higher AMH for maternal smoking after adjusting for socioeconomic status, broadly defined as education level (low, medium, high)(10). Our findings are consistent with two other studies that did not find in utero exposure to ETS to impact adult AMH levels in women, though neither of those adjusted for socioeconomic status, we were able to do this, and still found no association.…”
Section: Discussionmentioning
confidence: 99%
“…AMH levels vary by age (68) and may be associated with reproductive history (including age at menarche, parity and oral contraceptive use) (7, 9, 10), ethnicity (11), socioeconomic status (10) and polycystic ovarian syndrome (12). Epidemiologic and clinical studies suggest that reproductive health, as measured by AMH, may also be impacted by other environmental exposures, such as radiation and smoking (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone and androstenedione levels were comparable to levels in a control population. Other factors associated with serum anti-Mullerian hormone levels are oral contraceptive use, age at menarche, maternal smoking during gestation and socioeconomic status (Kerkhof et al, 2010). Growth hormone treatment has no detrimental effect on gonadal function in prepubertal short children born SGA (Boonstra et al, 2008;Lem et al, 2011).…”
Section: Puberty In Short Children Born Small For Gestational Agementioning
confidence: 99%